Inducing microstructural changes in Nafion by incorporating graphitic carbon nitride to enhance the vanadium-blocking effect. Issue 11 (2nd March 2018) - Wu, Chunxiao; Lu, Shanfu; Zhang, Jin; Xiang, Yan
Abstract : Two-dimensional graphitic carbon nitride (g-C3 N4 ) nanosheets are introduced into a Nafion matrix to prepare a 'vanadium-blocking' recast Nafion membrane for vanadium redox flow battery (VRFB) applications. Abstract : Two-dimensional graphitic carbon nitride (g-C3 N4 ) nanosheets are introduced into a Nafion matrix to prepare a 'vanadium-blocking' recast Nafion membrane for vanadium redox flow battery (VRFB) applications. After 0.2 wt% g-C3 N4 nanosheets are incorporated, the vanadium ion permeability of the composite membrane decreases from 3.3 × 10 −7 cm 2 min −1 to 3.8 × 10 −9 cm 2 min −1, which is a reduction of two orders of magnitude in comparison to the pristine recast Nafion membrane. This satisfactory result contributes to the physical blocking effect as well as the Donnan effect from the 2D morphology and functional amino groups of g-C3 N4 nanosheets. Notably, this work reveals that the g-C3 N4 nanosheets can help reinforce the vanadium-blocking effect by changing the microstructure of Nafion in addition to the well-known effects mentioned above. The g-C3 N4 nanosheets induce shrinkage in the original spherical structure of the ion cluster and generate a new lamellar structure. Correspondingly, the amorphous phase of Nafion is interrupted, and the membrane crystallinity is reduced. The VRFB with an optimized composite membrane achieves a high coulombic efficiency of 97% and an energy efficiency of 83% at a current density of 160 mA cm −2 . Meanwhile, the battery exhibited excellent lifetime stability during a 100 charge–discharge cycling test.